Legal Morality of Constitutional Court Decision Number 90/PUU-XXI/2023 Based on Pancasila - Wijaya, Made Hendra; Subawa, I Made; Palguna, I Dewa Gede; Astariyani, Ni Luh Gede; Sumadi, I Putu Sudarma (PT FORMOSA CENDEKIA GLOBAL, 2024)
Pancasila, as the source of legal morality of Indonesia, is used as the primary benchmark by Judges of the Constitutional Court in providing decision. The paper at hand explains that the constitutional court decision Number 90/PUU-XXI/2023 has moral weaknesses related to legal behaviour derived from Pancasila, specifically, First: Constitutional Court Decision had led to conflict and arising different views that potentially might cause disruption to Indonesia nation entity. Second: Constitutional Court Decision does not fully align with the Wisdom in Deliberation principle contained in the Fourth Principle of Pancasila. Third: Constitutional Court Judgment does not satisfy the sense of justice for Indonesian People. This paper employs a normative research method with a conceptual approach and a value-based approach.